2019
DOI: 10.1177/0271678x19855875
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular plasticity: Processes that lead to changes in the architecture of brain microvessels

Abstract: The metabolic demands of the brain are met by oxygen and glucose, supplied by a complex hierarchical network of microvessels (arterioles, capillaries, and venules). Transient changes in neural activity are accommodated by local dilation of arterioles or capillaries to increase cerebral blood flow and hence nutrient availability. Transport and communication between the circulation and the brain is regulated by the brain microvascular endothelial cells that form the blood–brain barrier. Under homeostatic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 199 publications
(290 reference statements)
4
34
1
Order By: Relevance
“…While developmental brain angiogenesis occurs simultaneously with BBB formation [35], during adulthood brain angiogenesis is typically associated with BBB breakdown [36][37][38]. Here we observed that both microvessels and capillaries restricted transport of 500 kDa dextran indicating the presence of a confluent endothelium with preserved barrier function (Fig.…”
Section: Hierarchical Model Of the Human Blood-brain Barriermentioning
confidence: 57%
See 1 more Smart Citation
“…While developmental brain angiogenesis occurs simultaneously with BBB formation [35], during adulthood brain angiogenesis is typically associated with BBB breakdown [36][37][38]. Here we observed that both microvessels and capillaries restricted transport of 500 kDa dextran indicating the presence of a confluent endothelium with preserved barrier function (Fig.…”
Section: Hierarchical Model Of the Human Blood-brain Barriermentioning
confidence: 57%
“…The culmination of brain angiogenesis during development results in a hierarchical BBB with profound heterogeneity in structure and phenotype [38,41,42]. However, after development, angiogenesis is generally restricted to pathological conditions which alter BBB structure and phenotype [36][37][38]. Here we developed an in vitro model of brain angiogenesis using iPSC-derived BMECs (dhBMECs) to study brain angiogenesis.…”
Section: Discussion Factors That Regulate In Vitro Brain Angiogenesismentioning
confidence: 99%
“…The culmination of brain angiogenesis during development results in a hierarchical BBB with profound heterogeneity in structure and phenotype [35][36][37]. However, after development, angiogenesis is generally restricted to pathological conditions which alter BBB structure and phenotype [37][38][39]. Here we develop an in vitro model of brain angiogenesis using iPSC-derived BMECs (dhBMECs) to study developmental and pathological angiogenesis.…”
Section: Discussion Factors That Regulate In Vitro Brain Angiogenesismentioning
confidence: 99%
“…Under homeostatic conditions angiogenesis is not prevalent in the adult brain; however, brain angiogenesis is associated with pathological conditions, including neurodegenerative disease, brain cancer, and stroke [37]. Production of reactive oxygen species (ROS) is associated with these conditions and may contribute to BBB disruption and pathological angiogenesis [60].…”
Section: Critical Chemical Cues Implicated In Developmental Brain Angmentioning
confidence: 99%
See 1 more Smart Citation